Doom : annihilation [videorecording (DVD)] - Giglio, Tony, 1971-; Giglio, Tony, 1971-; Manson, Amy, 1985-; Mafham, Dominic, 1968-; Allen-Gale, Luke (Universal Pictures Home Entertainment, 2019)
A lieutenant and an elite unit of Marines must stop a swarm of demons which are unleashed through an ancient portal on the darkest moon of Mars.